2016
DOI: 10.1371/journal.pone.0166454
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Novel Dermal Fibrosis Model Induced by Areca Nut Extract that Mimics Oral Submucous Fibrosis

Abstract: Oral submucous fibrosis (OSF) is an oral potentially malignant disorder and areca quid chewing is the main etiological factor. However, the molecular mechanism underlying OSF remains unclear, partly due to the lack of an appropriate animal model. The present study aimed to establish and characterize an animal model of areca nut extract (ANE)-induced skin fibrosis that mimics OSF. Mice were divided into 4 groups: the control group; the bleomycin group; and the ANE10 and ANE20 groups, which received 10mg/ml and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 32 publications
(22 reference statements)
1
17
0
Order By: Relevance
“…In our previous study, we showed that subcutaneous injection of ANE can induce dermal fibrosis within one month (Chiang et al, 2016). In this study, we found that injection of ANE into buccal tissues also induced fibrosis within one month, and pathological features similar to those of OSMF were observed.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…In our previous study, we showed that subcutaneous injection of ANE can induce dermal fibrosis within one month (Chiang et al, 2016). In this study, we found that injection of ANE into buccal tissues also induced fibrosis within one month, and pathological features similar to those of OSMF were observed.…”
Section: Discussionsupporting
confidence: 60%
“…We modified our previous ANE-induced dermal fibrosis model to investigate whether oral submucosal injection of ANE could induce OSMF (Chiang et al, 2016). Mice were treated with ANE, and the morphologic changes were analyzed on days 14 and 30 (Figure 1a, b).…”
Section: Oral Submucosal Injection Of Ane Increased the Buccal Submmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past few decades, accumulated studies have demonstrated that areca nuts can induce premalignant and malignant transformation of oral tissues. In animal model studies, areca nut extract (or the ingredient cocktail) can be an effective tumor initiator or promoter and can induce premalignant oral lesions, including submucosal fibrosis 9, 10 and squamous hyperplasia 11-13, or result in malignant transformation 13-16. For example, arecaidine displays a synergistic effect in the 7,12-dimethyl-benz(a)anthracene (DMBA)- induced tumor formation in the cheek pouch of hamster 15.…”
Section: Molecular Pathology Of Areca Nutmentioning
confidence: 99%
“…Currently, there was no well-established animal model to mimic the pathogenesis of OSF. These methods were either time consuming [29] or not suitable for studying fibrosis in the oral mucosae as the induced fibrosis occurred in the back [30]. Further studies are needed to examine the effect of targeting YBX1 on relief OSF symptoms in vivo.…”
Section: Discussionmentioning
confidence: 99%